Wild Land Tax Fieri facias: Fulton County, GA. - Daniel Lott - State of Georgia, Wayne County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1877)
Tax Receipt, Wayne County, 1877. Wild Land tax receipt, lot no. 1666, Wayne County, Georgia to James Knox. Comptroller General Office. October 3, 1877. 2 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Court records; Records and correspondence; Wayne County (Ga.); Fulton County (Ga.)